Development of Acid Base E-Module Based on Guided Discovery Learning to Improve Digital Literacy Skills of Senior High School Phase F Students - Haifa Hafifah; Yerimadesi Yerimadesi; Alizar Alizar; Desy Kurniawati (Postgraduate, University of Mataram, 2025)
This study aims to analyze the validity, practicality, and effectiveness of the acid-base e-module based on guided discovery learning on students' digital literacy skills. The development model used is the Plomp development model. The developed e- module was validated by three lecturers and two chemistry teachers. The module's practicality test was carried out by three chemistry teachers and 33 high school students. The module's effectiveness test was carried out using the pre-experimental method with a non-equivalent control group design. The validity test is explained using Aiken's V formula. The overall validity test results were obtained of 0.91 with a valid category. The results of the e-module practicality test carried out by teachers and students were 89.4 and 87.09% with a very practical category. The average N-Gain value in the experimental class was 0.75, which is in the high category. Based on the results of data analysis, it can be concluded that the acid-base e-module, based on guided discovery learning that was developed, is valid, practical, and effective in improving the digital literacy skills of Phase F (Grade XI) high school students